THE IMPACT OF YOGA ASANAS ON COLLEGE WOMEN’S PHYSICAL FITNESS (International Journal of Food and Nutritional Sciences, 2023)
The best thing that parents can do for their daughters is to encourage them to take partin extracurricular activities like “Physical Fitness” classes and team sports. This will helptheir daughters in the long run. Over the course of the past several decades, “PhysicalFitness” (P.F.) has steadily become more of a priority, especially in educational institutionssuch as high schools and universities.